Factors Affecting Teacher Digital Competence : An Exploratory Factor Analysis - Windasari, Windasari; Karwanto, Karwanto; Supriyanto, Supriyanto; Setiani, Puji (Jurnal Kependidikan, 2022)
This study aims to analyze the factor affecting the teacher competence in mastering digital technology in classroom learning during face-to-face learning in elementary schools in Lamongan district. This study used a quantitative approach using exploratory factor analysis (EFA) techniques. EFA is used to determine indicators related to teacher competence in mastering digital technology. The population of this study were teachers in Lamongan district. The sample of this research is 60 respondents with a cluster sampling method. The research stages include 1) instrument development, 2) instrument validation, 3) data collection, 4) data analysis, and 5) reporting. The results showed that there were 4 factors in mastering digital technology for teachers, namely collaboration, personal development, data literacy and information literacy. Collaboration and personal development in increasing digital competence influence on teacher performance in the teaching process. Teachers have numerous teaching materials due to collaboration using digital platforms.